(untitled) (Palíndromo, 2024)
This article proposes an analysis of Povo da lua, povo de sangue (1983), a photofilm directed by Marcelo Tassara and based on Claudia Andujar’s photographs of the Yanomami people. The aim is to problematize the social position and political effectiveness of the film, considering its intentions, characteristics, and ambiguities. The text argues that the film carries a “desire for salvation” and, at the same time, does not hide the connection between the photographic operation and colonial violence, since the film is situated between its aesthetic and political powers, its responsibilities and their limits.